Understanding the Key Factors That Influence Efficient Water-Saving Practices among Tourists: A Mediterranean Case Study - Maria Torres-Bagur (Water, 2020)
The future of tourism activity is dependent on its ability to adapt to the effects of climate change. One of the most notable effects in the Mediterranean area will be water shortages in a scenario marked by increasing demand for this resource. While this situation will affect numerous economic sectors, it will have a severe impact on the tourism industry, which relies heavily on water. The aim of this study was to analyze water-saving practices among guests at campsites, hotels, and rural lodgings in the Muga river basin and investigate the factors that influence these practices. We conducted 752 surveys and found that differences in practices were influenced by reason for stay, type of accommodation, and geographic origin. A greater understanding of how sociodemographic and motivational characteristics influence water-saving behavior by guests at different types of tourist accommodation is essential for designing targeted strategies for improving environmental awareness and water-saving habits.